Analysis of the impact of operational cost cutting strategies on financial performance. : a case study of Zimbabwe Alloys Chrome (under judicial management) - Tanyanyiwa, Tatenda Trishia (Midlands State University, 2020)
The research aims to analyse the impact of operational cost cutting strategies on financial performance. A case study of Zimbabwe Alloys Chrome (under judicial management) was used to analyse the impact of the operational cost cutting strategies implemented, determining factors that affect the successful implementation of operational cost cutting strategies. Literature from different scholars and authors on cost cutting was reviewed in this study. The study made use of questionnaires and interviews to collect data from the organization. The study targeted 26 ZAC members, a total of 22 questionnaires were distributed to ZAC staff and 18 were returned earning 82% and 3 individuals were interviewed inspiring a 100% response rate. Data was presented using tables, graphs and analysis was made resulting in conclusions being drawn. Upon data analysis, it was revealed that ZAC cost cutting measures positively affects the financial performance in the long run but in the short run the financial woes will worsen before they improve. The recommendations passed by the researcher included the improvement of current cost cutting measures and continuation with the application of the cost cutting measures. The researcher also recommended ZAC to implement controls so as to make sure that all current cost control procedures and policies are adhered to, budget formulation and introduction of incentives and bonuses for meeting budgets.